Microsoft Windows scripting with WMI : self-paced learning guide - Wilson, Ed (Microsoft Press, 2005)
Get the inside track on how to write system administration scripts with Windows Management Instrumentation (WMI), straight from Microsoft scripting experts. This practical learning guide teaches how to use WMI scripting techniques to gain control over your Microsoft WindowsÃ¢??based, IIS-based, and Microsoft Exchange ServerÃ¢??based environmentsÃ¢??all at your own pace. Build practical skills on everything from understanding the ins and outs of WMI and producing your first WMI Script to writing advanced WMI scripts that automate the management of systems, network services, files, printers, the registry, network services, and more. The companion CD features the complete eBook, 140 sample scripts, and timesaving scripting tools, plus more than 500 bonus scripts! Visit the catalog page for Microsoft® Windows® Scripting with WMI: Self-Paced Learning GuideVisit the errata page for Microsoft® Windows® Scripting with WMI: Self-Paced Learning Guide.